Neuro Linguistic Programming and Organizational Resilience - Cruz Montero, Juana María; Avila Vasquez, Marilu; Bringas Salvador, Jorge Luis; Tejada Estrada, Gina Coral (Revista Venezolana de Gerencia, 2021)
Analyzing the relationship between Neuro-Linguistic Programming (NLP) and organizational resilience is the objective of this descriptive-documentary theoretical review research. The results allow us to reflect on neurolinguistic programming and how it constitutes an invaluable strength for overcoming potential adversities and unexpected change processes that may arise within an organization regardless of its nature, that is, from it organizational resilience is required. It is concluded that Neuro-Linguistic Programming is a tool whose implementation in the organizational environment has proven to be of indisputable help to achieve an adequate functioning that results in resilient capacity